Persistence and Stability for a Generalized Leslie-Gower Model with Stage Structure and Dispersal - Hai-Feng Huo; Zhan-Ping Ma; Chun-Ying Liu (Abstract and Applied Analysis)
A generalized version of the Leslie-Gower predator-prey model that incorporates the prey structure and predator dispersal in two-patch environments is introduced. The focus is on the study of the boundedness of solution, permanence, and extinction of the model. Sufficient conditions for global asymptotic stability of the positive equilibrium are derived by constructing a Lyapunov functional. Numerical simulations are also presented to illustrate our main results.